Effect of Plant Growth Regulators on Mass Propagation of Strawberry (Fragaria sp.): Mass production of strawberry plantlets in vitro (Journal of the Bangladesh Agricultural University, 2024)
Efficient in vitro regeneration protocols for strawberries are crucial for accelerating the propagation of superior cultivars and improving overall productivity through controlled manipulation of plant growth regulators. This study investigated the influence of different concentrations and combinations of plant growth regulators on in vitro regeneration process of strawberries. BARI Strawberry-1 runner tips were sterilized and placed on Murashige and Skoog medium (MS) supplemented with various combinations of cytokinins, including 6-benzylaminopurine (BAP) and kinetin (KIN), to initiate shoot growth. Notably, the combination of 1.5 mg/L BAP + 1.0 mg/L KIN led to the shortest duration for shoot initiation (9 days), resulting in the highest number of shoots per explants (6.33), longest shoot length (2.87 cm), and maximum number of leaves per shoot (4.00). Additionally, this combination also exhibited the highest rate of shoot regeneration (70.33%). Subsequently, the proliferated shoots were transferred to MS medium supplemented with various concentrations and combinations of auxins, specifically 3-indolebutyric acid (IBA) and 1-naphthaleneacetic acid (NAA), for root induction. The in vitro regenerated shoots cultured in MS medium supplemented with 1.5 mg/L IBA + 1.0 mg/L NAA showed the shortest duration for root formation (8 days), the highest number of roots per explants (4.00), and the longest root length (2.77 cm). Furthermore, this combination also resulted in the highest rate of root regeneration (40%). These findings contribute valuable insights for the mass production of healthy strawberry plantlets using in vitro culture techniques.J Bangladesh Agril Univ 22(2):178-184, 2024